Publication practices and responsible authorship: a review article - Elvis E. Tarkang; Margaret Kweku; Francis B. Zotor (AOSIS, 2017)
Dissemination of research findings through the publication of one's work or a group of contributors is an important part of the research process, as this allows the passing on of benefits to a much wider community. In whatever evocative form this dissemination may take, the onus lies on the author(s) to ensure adherence to the code of ethics as it pertains to the integrity of the information being put out. We publish because we want our findings to be adapted into practice and application, or in some cases may be relevant to policy makers in decision-making. To a large extent in the field of academia, successful publication improves opportunities for academic funding and promotion whilst enhancing scientific and scholarly achievement and repute. A situation may be compromised where intellectual contributions to a scientific investigation do not adhere to the four key guidelines of scholarship, authorship, approval and agreement as well as the protocols of ensuring good publication ethics. The objective of this review is to lay emphasis on universal standards for manuscript authorship and to fostering good practices. This in our view will bring authorship credit and accountability to the attention of our colleagues and readers at large. To achieve this, a systematic and critical review of the literature was undertaken. Electronic databases, academic journals and books from various sources were accessed. Several key search terms relating to responsible authorship, common authorship malpractices, conflict of interest, universal publication guidelines and other authorship related issues, were used. Only references deemed useful from relevant texts and journal articles were included. In this paper, the authors have sought to highlight the pitfalls researchers sometimes entangle themselves within an act of compromise thereby impinging on the ethical and professional responsibilities for the content of a paper under consideration. This article presents the case that authorship has a strong currency that brings not only personal satisfaction but also career rewards based on publication counting. In all cases described here, a universal standard for manuscript authorship will be critical in fostering good practices. As you write and review manuscripts, keep these good practices in mind, and consider ways to bring authorship credit and accountability to the attention of your colleagues and readers.